Analisis Efisiensi Waktu Layanan Pada Sistem Administrasi Perpustakaan Menggunakan Metode Sistem Antrian - ', Hendra; Nasution, Helfi (ELKHA : Jurnal Teknik Elektro, 2012)
Abstract Library administration system that includes member registration process and recording of transactions that are manually provide time constraints in providing services to member libraries. In addition, an effect also on the number of members who would like to borrow a book because they have to wait to be served. A computerized library administration system will provide a solution to these problems and the use of barcode scanners will speed up the process of library services. Furthermore, the library administration system using the method of queuing systems is designed to improve library service system. Keywords - queuing systems, library service system